Poly(A) RNA‐binding proteins and polyadenosine RNA: new members and novel functions. (30th April 2014) - Wigington, Callie P.; Williams, Kathryn R.; Meers, Michael P.; Bassell, Gary J.; Corbett, Anita H.
Abstract : Poly(A) RNA‐binding proteins (Pabs) bind with high affinity and specificity to polyadenosine RNA. Textbook models show a nuclear Pab, PABPN1, and a cytoplasmic Pab, PABPC, where the nuclear PABPN1 modulates poly(A) tail length and the cytoplasmic PABPC stabilizes poly(A) RNA in the cytoplasm and also enhances translation. While these conventional roles are critically important, the Pab family has expanded recently both in number and in function. A number of novel roles have emerged for both PAPBPN1 and PABPC that contribute to the fine‐tuning of gene expression. Furthermore, as the characterization of the nucleic acid binding properties of RNA‐binding proteins advances, additional proteins that show high affinity and specificity for polyadenosine RNA are being discovered. With this expansion of the Pab family comes a concomitant increase in the potential for Pabs to modulate gene expression. Further complication comes from an expansion of the potential binding sites for Pab proteins as revealed by an analysis of templated polyadenosine stretches present within the transcriptome. Thus, Pabs could influence mRNA fate and function not only by binding to the nontemplated poly(A) tail but also to internal stretches of adenosine. Understanding the diverse functions of Pab proteins is not only critical to understand how gene expression is regulated but also to understand the molecular basis for tissue‐specific diseases that occur when Pab proteins are altered. Here we describe both conventional and recently emerged functions for PABPN1 and PABPC and then introduce and discuss three new Pab family members, ZC3H14, hnRNP‐Q1, and LARP4. WIREs RNA 2014, 5:601–622. doi: 10.1002/wrna.1233 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications RNA Processing > 3' End Processing